The investigation of simplified excavation method on tunnel behaviour - Yoon, Chan Yip, 1991-, author; Siti Norafida Jusoh, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2017